Аutosomal recessive limb-girdle muscular dystrophy type 2A: two cases in Ukraine with different age of onset - Antipkin, Yu.H.; Kyrylova, L.H.; Miroshnykov, O.O.; Yuzva, O.O.; Orzheshkovskyi, V.V.; Nechay, A.F. (Medicni Perspektivi, 2021)
The paper reports on two cases of young women from Ukraine with autosomal recessive limb-girdle muscular dystrophy type 2A with different age of symptoms onset and an absence of any family history presented with gradual onset of proximal muscle weakness in four limbs and thinning of shoulders, arms and thighs. Both patients had elevated creatine phosphokinase level and c.550delA mutations in CAPN3 gene. Sequence analysis and deletion/duplication testing of the 159 genes from skeletal muscles disease testing panel of 5-year-old girl identified deletion of exon 8 (heterozygous) and c.550delA (p.Thr184Argfs*36) mutation (heterozygous), were in CAPN3 gene. Magnetic Resonance Imaging of soft tissue of the proximal lower extremities was performed which showed signs of symmetrical atrophic changes in the major adductor muscle, the long and short adductor muscles, the semitendinosus muscle of the thigh, as a manifestations of autosomal recessive limb-girdle muscular dystrophy type 2A. Homozygous, pathogenic variant of the defect in the CAPN3 gene c.550del (p.Thr184Argfs * 36) was identified in a 25-year-old woman. Type 2A is the most common form of limb-girdle muscular dystrophy, accounting for about 30% of cases. The autosomal recessive limb-girdle muscular dystrophy type 2A is on caused by mutations in the CAPN3 gene, and it is characterized by selective atrophy and weakness of proximal limb and girdle muscles. The age of onset of muscle weakness is extremely variable; the most common being between 8 and 15 years, although it can range between 2 and 50 years. The diagnosis can be suspected by findings on a muscle biopsy or when a doctor experienced in muscular dystrophy examines you. A serum creatine kinase blood test may also show raised levels which indicate a problem in the muscles. The diagnosis has to be confirmed by means of identifying a mutation in the CAPN3 gene which is done on a deoxyribonucleic acid sample from a blood test. To date there are no specific treatments for limb-girdle muscular dystrophy, however careful management of the symptoms of the condition can improve a person’s quality of life. Joint contractures (tightening) can occur in limb-girdle muscular dystrophy and therefore regular physiotherapy is recommended.